PENGARUH PEMBERIAN PUPUK KANDANG AYAM PADA TANAH LATOSOL TERHADAP PERTUMBUHAN SEMAI MAHONI DAUN LEBAR - Wafa, Ali; Asmarahman, Ceng; Indriyanto, Indriyanto (MAKILA, 2023)
Latosol soil has poor chemical properties such as low cation exchange capacity, acid-base character, and low nutrients. The use of latosol soil as a medium for forest plant growth requires the provision of organic matter including the use of chicken manure. The use chicken manure has been widely used and researched. However, the growth of mahony seedlings has not been large or recorded. The study used a completely randomized design method. The treatments consisted of 4 level, control (pure latosol soil), 10% chicken manure, 20% chicken manure, 20% chicken manure, and 30% chicken manure. Growth variables of seedling consisted of stem height, stem diameter, number of leaves, shoot dry weight, root dry weight, total dry weight, root shoot ratio, seed quality index, and chemical properties chicken manure and latosol soil. The data were analyzed by analysis of variance (ANOVA) and HSD test at 5% significance level. The results showed that 10% chicken Manure treatment had the best affect on stem height (29.92 cm), number of leaves (15.40 strands), shoot dry weight (5.10 g), total dry weight (7.30 g), root shoot ratio (2.55), and seeds quality index (0.22).